ORGANIZATION OF THE EDUCATIONAL PROCESS IN THE PRESCHOOL EDUCATIONAL ORGANIZATION - Abdukhamidova Madinakhan Aslonbek kizi; Khallakova Maqsudakhan (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article provides information about the work carried out in preschool educational organizations, educational processes, determination and development of positive qualities in students.